ONIROS: minha trajetória na Medicina UFSCar - Alves, Guilherme de Oliveira (Universidade Federal de São Carlos, 2020)
This narrative tells about how was my passage through the Medicine course at UFSCar, pointing out my struggles, activities that I joined and how it affected me, contributing in order for me to be where I’m at today, close to the end of my graduation and being the foundation to how I will continue my development from now on.
ONIROS: my journey through mediccal school at UFSCar
Keywords: Medicina; Vivências; CIENCIAS DA SAUDE::MEDICINA